The Effect of Group Guidance Method using Sociodrama Technique to Improve Students' Self-Confidence - Reza Pahlevi; Hartono Hartono; Lenia Nawang Arum (Indonesian Journal of Guidance and Counseling Studies, 2025)
The purpose of this study was to determine whether there was an increase in students' self-confidence through sociodrama. This research was conducted at SMP Muhammadiyah 3 Yogyakarta in 2022. The subjects in this class action research were third-grade students at SMP Muhammadiyah 3 Yogyakarta with 30 students. In this research, researchers used the questionnaire method as a method of obtaining data in a questionnaire about student self-confidence. The research data were analyzed statistically using the t-test formula. The results of data analysis showed that the implementation of group guidance services using sociodrama method can increase the student’s confidence. The results of the study obtained the conclusion that group guidance services with sociodrama methods were able to increase self-confidence in students.